Reconstructing Medical Problem Solving Competence: MACCORD - Kraus, D.; Petkoff, B.; Mannebach, H.; Kirkby, S. (Methods of Information in Medicine, 1993)
The building of medical knowledge-based systems involves the reconstruction of methodological principles and structures within the various subdomains of medicine. ACCORD is a general methodology of knowledge-based systems, and MACCORD its application to medicine. MACCORD represents the problem solving behavior of the medical expert in terms of various types of medical reasoning and at various levels of abstraction. With MACCORD the epistemic and cognitive processes in clinical medicine can be described in formal terminology, covering the entire diversity of medical reasoning. MACCORD is close enough to formalization to make a significant contribution to the fields of medical knowledge acquisition, medical didactics and the analysis and application of medical problem solving methods.
Keywords: Methodology; Medical Reasoning; Problem Solving; Knowledge-Based Systems; Knowledge Acquisition